(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article explores the expression of national and universal values in the literary works of William Shakespeare and Alisher Navoi from a comparative perspective. Both authors represent significant cultural and literary traditions and have made an invaluable contribution to the development of world literature. The study analyzes how the writers portray human values such as justice, love, morality, dignity, and social harmony while simultaneously reflecting the national identity and cultural worldview of their societies. Using comparative literary analysis and textual interpretation, the article examines selected works of the two authors to identify similarities and differences in the artistic representation of ethical ideals. The results show that despite cultural and historical differences, both writers emphasize universal human values and ethical responsibility. At the same time, their works reflect specific national traditions, philosophical perspectives, and social conditions. The research highlights the importance of comparative literary studies in understanding the interaction between national identity and universal humanistic ideals in world literature.